STATUS PEKERJAAN IBU DENGAN KETEPATAN WAKTU PEMBERIAN IMUNISASI PENTAVALEN PADA BATITA DI WILAYAHKERJA PUSKESMAS TELAGA BIRU KABUPATEN GORONTALO - Andi Akifa Sudirman; Muriyati Rokani; Sulastri Ibrahim (Universitas Muhammadiyah Gorontalo, 2020)
This research was conducted at Telaga Biru health centre work area. The objective was to identification The relationship of mother’s Occupation status with the Timeliness of giving Pentavalent Immunization on infants at Telaga Biru Health Centre Work Area. Populations were 108 infants. The samples are 36 respondents. This research was conducted in 2 weeks. The design used observational analytic with cross sectional study approach and collecting data from respondents used questionnaire form. The Chi Square test result obtained significant value ρ=0,010 < 0,05, Ho is rejected which means there is significance relationship between variable of mother’s Occupation status with Timeliness of giving Pentavalent Immunization.